2019
DOI: 10.1021/acs.joc.9b01354
|View full text |Cite
|
Sign up to set email alerts
|

Photocycloaddition of S,S-Dioxo-benzothiophene-2-methanol, Reactivity in the Solid State and in Solution: Mechanistic Studies and Diastereoselective Formation of Cyclobutyl Rings

Abstract: The formation of cyclobutane rings is a promising strategy in the development of potential drugs and/or synthetic intermediates, typically challenging to obtain due to their constrained nature. In this work, the [2 + 2] photocycloaddition reaction of S,S-dioxobenzothiophene-2-methanol was explored in microcrystalline powders and its outcome was compared to that observed in solution. It was found that the molecular constraints inherited within the crystal lattice provide an optimal environment that leads to pho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 60 publications
1
6
0
Order By: Relevance
“…Regarding proposed step 3, temperature- and salt-dependent transitions are known, and an A- to Z-form duplex transition was recorded in a temperature dependent manner, where the Z-form was generated at 45 °C using high monovalent cation concentrations (NaClO 4 , up to 6 M). 23 Transitions that are similar to those reported here are not common; however, something similar, albeit less intense, was reported with DNA containing pyrene units at the nucleobase. 49 All studies describing such arrays do not exhibit the stabilization observed in this work, presumably because the salt concentration was increased substantially herein.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…Regarding proposed step 3, temperature- and salt-dependent transitions are known, and an A- to Z-form duplex transition was recorded in a temperature dependent manner, where the Z-form was generated at 45 °C using high monovalent cation concentrations (NaClO 4 , up to 6 M). 23 Transitions that are similar to those reported here are not common; however, something similar, albeit less intense, was reported with DNA containing pyrene units at the nucleobase. 49 All studies describing such arrays do not exhibit the stabilization observed in this work, presumably because the salt concentration was increased substantially herein.…”
Section: Discussionsupporting
confidence: 88%
“…In regards to the observed transition, and given the gathered information, we are proposing a model where (1) the benzothiophene units may interact with each other, stronger in higher monocation content, and the nucleobase interactions (base pair H-bonding or π–π stacking) are disrupted; (2) upon heating, the abnormal base pair H-bonding interactions show signs that disruption/breakage starts to occur; (3) the hydrophobic benzothiophene rings aid to maintain the structure in place and allow for another internal H-bond rearrangement (much like a duplex transition, A- to Z-form) into a more thermodynamically stable structure, resulting in optimal nucleobase interactions; and (4) increased temperatures lead to denaturation of the duplex. Regarding proposed step 3, temperature- and salt-dependent transitions are known, and an A- to Z-form duplex transition was recorded in a temperature dependent manner, where the Z-form was generated at 45 °C using high monovalent cation concentrations (NaClO 4 , up to 6 M) . Transitions that are similar to those reported here are not common; however, something similar, albeit less intense, was reported with DNA containing pyrene units at the nucleobase .…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…[6] However, these reactions were only performed in solutions. Resendiz et al [7] reported the photodimerization of BTO derivatives in the solid-sate and elucidated the impact of reaction conditions on the structures of the photodimers. In comparison with the BTO derivatives reported by Resendiz et al, P-BTO has a bulky phenyl substitute.…”
mentioning
confidence: 99%